Lineage, cosmology, and sacred access: Reinterpreting Nawa Sanga in the Royal Compounds of Blahbatuh (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This research is grounded in the prevailing inclination within studies of Balinese palace architecture to interpret the Nawa Sanga cosmology chiefly as a symbolic framework of orientation, while its function as a governing apparatus in organizing hierarchical access and sacred spatial domains has not been thoroughly explored. In reality, the configuration of sacred space within a palace is shaped not solely by cosmological gradients but also by genealogical structures (pasemetonan), which establish ritual legitimacy, authority, and rights to spatial occupation. This study seeks to reconceptualize Nawa Sanga as a socio-spatial governance system that organizes hierarchical access and sacred space within Puri Ageng Blahbatuh and Puri Kaleran Jelantik. The research adopts a qualitative multiple case study methodology, incorporating spatial observation, architectural documentation, in-depth interviews, and genealogical analysis. The results reveal that hierarchical access and sacred spatial organization are generated through the interaction of three interconnected layers: cosmological orientation as a normative framework, genealogical structure as the foundation of legitimacy, and spatial mechanisms, such as thresholds and circulation patterns, as instruments of regulation. These findings affirm that Nawa Sanga operates not merely as a symbolic construct but as a regulatory system that sustains and reproduces social hierarchy through stratified control over access to sacred space.